Introducción al estudio de la política de cooperación portuguesa - Nunes Belo, João Eduardo (Revista Española de Desarrollo y Cooperación, 2023)
The article presents the portuguese development cooperation policy, tied to portuguese speaking areas, such as several african countries or Timor. It explains the reform undertaken in the last years in order to improve coordination among different agents acting in cooperation, and it presents each one of them. It also presents an evaluation of the recommendations made by the DAC (of which Portugal is a member since it was created) in the different exams of the Portuguese policy.